Schadenfreude as a consumption‐related emotion: Feeling happiness about the downfall of another's product - Sundie, Jill M.; Ward, James C.; Beal, Daniel J.; Chin, Wynne W.; Geiger‐Oneto, Stephanie (Journal of Consumer Psychology, 2009)
AbstractEmotional antecedents of schadenfreude—joy experienced when observing another's downfall—were investigated in a status consumption context. Across 3 studies, status product failure produced schadenfreude and led to intentions to spread negative word‐of‐mouth (studies 1, 2), and increased negative affect and overall negative attitudes toward the status brand (study 3). Furthermore, studies 1 and 2 suggest that envy (particularly of social attention) can lead to schadenfreude by transmuting into hostile emotions. Finally, these studies suggest that schadenfreude in a consumption context can be precipitated by factors such as degree of target advantage and flaunting of the status product.